PENINGKATAN HASIL BELAJAR BIOLOGI PADA POKOK BAHASAN SISTEM EKSKRESI MANUSIA DI KELAS IX-A SMP NEGERI 1 PRAJEKAN MELALUI MODEL PEMBELAJARAN - Triastuti Desy Artika; Firman Jaya (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
The Examples Non Examples learning model is a learning model using images as a learning medium, which aims to encourage students to learn to think critically by solving the problems contained in the examples of the images presented. Making it easier for students to understand the material. The use of image media is structured and designed so that children can analyze the image into a form of a brief description of what is in the picture. The use of the Examples Non Examples learning model emphasizes the context of student analysis. This study aims to improve the learning outcomes of biology on the subject of the human excretion system in class IX-A SMP Negeri 1 Prajekan. The low completeness of biology learning outcomes in class IX-A students of SMP Negeri 1 Prajekan is due to the KKM that must be taken> 70 out of 36 students only 25 students whose average score is> 70 which should be classical> 75% completeness criteria. It is also difficult to involve students actively due to the lack of students being directly involved in solving a problem in a material because teachers often use the lecture method so that students are only listeners. To determine the success of the education and teaching process in schools in changing the behavior of students towards the expected educational goals, it is necessary to assess learning outcomes. The aspects of achieving learning outcomes include three aspects, namely: cognitive aspects, affective aspects, and psychomotor aspects. This type of research is Classroom Action Research (CAR). This type of research is carried out in 2 cycles, each cycle includes 4 stages of activity, namely: 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. Based on the results of the analysis, it can be concluded that learning using the Examples Non Examples learning model in the first cycle, classical completeness in the cognitive domain is 75%, while in the affective domain it is 80.56% and in the psychomotor domain it is 80.55%, in the second cycle it is obtained The increase in learning outcomes from the cognitive domain was 86.36% while in the affective domain it was 83.33% and in the Psychomotor domain it was 86.11%. From this learning there was an increase in learning outcomes in the cognitive aspects of 11.76%. In the affective aspect, it was 2.77% and psychomotor was 5.89%. The suggestion that the researcher can convey is that the application of the Examples Non Examples learning model should be used as an alternative to be applied to existing learning, so that students can understand the concept of biology well and can be applied to real life.